Representasi Laki-laki Ladyboy dalam Karya Tari SHEMALE: Satu Anomali dalam Prilaku Laki-laki Minangkabau - Dendi Chairi; Indrayuda Indrayuda (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This article aims to reveal the problem of deviant behavior in Minangkabau men. According to tradition and culture, Minangkabau men are men who are based on traditional behavior coded as syarak and syarak coded as khitabullah, meaning that Minangkabau men are men who behave according to Islamic customs and norms. In the dance work entitled